A non-invasive technique for recording the Cardiac activity of the tropical-subtropical mangrove Oyster Crassostrea brasiliana - Bakhmet, Igor; Abessa, Denis M.S. [UNESP]; Buruaem, Lucas M. [UNESP]; Bonnail, Estefanía (My University, 2015)
In this study, we searched the electric signal of the heart of Crassostrea brasiliana; the cardiac activity of 7 individuals was monitored and recorded for a week. The heart beat rates were clearly detected and showed low variation. The technique presented good potential to be used in oysters.
Keywords: Heart beat rate; Mollusk; Oyster; Physiology